Chemical Composition of Earthworm (Eisenia foetida) Co-Dried with Vegetable Meals as an Animal Feed (2019)
To evaluate the chemical composition of the earthworm (Eisenia foetida) co-dried (EW) with vegetable meals (VM) as animal feed ingredient, the blends were mixed with wheat bran (WB), rice powder (RP), corn meal (CM) and soy cake meal (SCM) in proportions of 85:15; 75:25 and 65:35. The dry matter (DM), crude protein (CP), crude fat (CFA), crude fiber (CF), ashes and nitrogen-free extract (NFE) of the ingredients and final mixtures were determined. All the mixtures resulted with a high content of DM (≥90.00 %). No significant differences among the proportions were revealed (P>0.05). In addition, the higher inclusion of the earthworm in the proportions (85:15) increased (P<0.05) the CP (54.70 %), CFA (7.28 %), and ashes (10.20 %), mainly when mixed with SCM, CM, and RP, respectively. However, the use of vegetable meals proportionally increased the CF (7.31 %), and NFE (52.62 %), mainly with the proportion of 65:35 and with RP and CM, respectively (P<0.05). The results showed that the vegetable meals (WB, RP, CM, and SCM) are useful to co-dry the earthworm to be use for animal feed. It is concluded that the most appropriate proportion (VM:EW) will depend on the animal species, productive stage and market requirement.